The Early Expression of HLA-DR and CD64 Myeloid Markers Is Specifically Compartmentalized in the Blood and Lungs of Patients with Septic Shock - Tomasz Skirecki; Małgorzata Mikaszewska-Sokolewicz; Grażyna Hoser; Urszula Zielińska-Borkowska (Mediators of Inflammation)
Identification of reliable biomarkers is key to guide targeted therapies in septic patients. Expression monitoring of monocyte HLA-DR and neutrophil CD64 could fulfill the above need. However, it is unknown whether their expression on circulating cells reflects the status of tissue resident cells. We compared expressions of HLA-DR and CD64 markers in the circulation and airways of septic shock patients and evaluated their outcome prognostic value. The expression of CD64 on neutrophils and HLA-DR on monocytes was analyzed in the peripheral blood and mini-bronchoalveolar lavage fluid cells by flow cytometry. Twenty-seven patients with septic shock were enrolled into the study. The fluorescence intensity of HLA-DR on circulating monocytes was 3.5-fold lower than on the pulmonary monocytes (p=0.01). The expression of CD64 on circulating and airway neutrophils was similar (p=0.47). Only the expression of CD64 on circulating neutrophils was higher in nonsurvivors versus survivors (2.8-fold; p=0.031). Pulmonary monocytes display a higher level of HLA-DR activation compared to peripheral blood monocytes but the expression of neutrophil CD64 is similar on lung and circulating cells. Death in septic patients was effectively predicted by neutrophil CD64 but not monocytic HLA-DR. Prognostic value of cellular activation markers in septic shock appears to strongly depend on their level of compartmentalization.